2016
DOI: 10.3892/or.2016.5160
|View full text |Cite
|
Sign up to set email alerts
|

Let-7a suppresses cell proliferation via the TGF-β/SMAD signaling pathway in cervical cancer

Abstract: Cervical cancer is the second most commonly diagnosed type of cancer among women after breast cancer. Recent research has addressed the role of microRNAs in cervical cancer. In the present study, we aimed to determine the effect of let‑7a on the regulation of the cell proliferation of cervical cancer and the related signaling pathway. Real‑time RT‑PCR was used to detect the expression of let‑7a in the blood of cervical cancer patients and normal controls. The expression of let‑7a was also assessed in cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In HeLa and SiHa CC cells, smad7 is a target of miR-519d, an oncogenic miRNA that promotes metastasis [222]. Tumor suppressor let-7a targets smad4 to suppress TGF-β-mediated proliferation of CC cells [223]. In EC cells, smad3 is targeted by miR-23a to modulate TGF-β-mediated EMT [224].…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%
“…In HeLa and SiHa CC cells, smad7 is a target of miR-519d, an oncogenic miRNA that promotes metastasis [222]. Tumor suppressor let-7a targets smad4 to suppress TGF-β-mediated proliferation of CC cells [223]. In EC cells, smad3 is targeted by miR-23a to modulate TGF-β-mediated EMT [224].…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%
“…Plenty of studies have pointed to the involvement of miRNAs in various diseases, including cancer, (3)(4)(5)(6) heart diseases, (7,8) lung diseases, (9,10) nervous system disorders, (11,12) and even genetic diseases. (13)(14)(15) MicroRNAs can be transported in the extracellular circulation in several ways, including: (1) complexed with highdensity lipoproteins (HDL) or the Ago2 protein; (16) (2) encapsulated within microvesicles; (17) (3) accumulated in apoptotic bodies; (18) and (4) packaged within exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations in adipose tissue and variations in hormone secretion can cause many metabolic phenotypes, including T2D, 2 cardiovascular diseases 3 and obesity. 9 In addition, Wu et al 10 revealed that let-7a suppresses cell proliferation by targeting TGFBR1 in cervical cancer, 10 and Li et al 11 found that miR-9-5p facilitates cell growth and development by attenuating TGFBR2 in non-small-cell lung cancer. 7 The transforming growth factor-β (TGF-β) family contains three isoforms, TGF-β1, TGF-β2, and TGF-β3.…”
Section: Introductionmentioning
confidence: 99%